PtK1 cells contain a nondiffusible, dominant factor that makes the Golgi apparatus resistant to brefeldin A (The Rockefeller University Press, 1991)
Brefeldin A (BFA) was shown in earlier studies of numerous cell types to inhibit secretion, induce enzymes of the Golgi stacks to redistribute into the ER, and to cause the Golgi cisternae to disappear. Here, we demonstrate that the PtK1 line of rat kangaroo kidney cells is resistant to BFA. The drug did not disrupt the morphology of the Golgi complex in PtK1 cells, as judged by immunofluorescence using antibodies to 58- (58K) and 110-kD (beta-COP) Golgi proteins, and by fluorescence microscopy of live cells labeled with C6-NBD-ceramide. In addition, BFA did not inhibit protein secretion, not alter the kinetics or extent of glycosylation of the vesicular stomatitis virus (VSV) glycoprotein (G-protein) in VSV- infected PtK1 cells. To explore the mechanism of resistance to BFA, PtK1 cells were fused with BFA-sensitive CV-1 cells that had been infected with a recombinant SV-40 strain containing the gene for VSV G- protein and, at various times following fusion, the cultures were exposed to BFA. Shortly after cell fusion, heterokaryons contained one Golgi complex associated with each nucleus. Golgi membranes derived from CV-1 cells were sensitive to BFA, whereas those of PtK1 origin were BFA resistant. A few hours after fusion, most heterokaryons contained a single, large Golgi apparatus that was resistant to BFA and contained CV-1 galactosyltransferase. In unfused cells that had been perforated using nitrocellulose filters, retention of beta-COP on the Golgi was optimal in the presence of cytosol, ATP, and GTP. In perforated cell models of the BFA-sensitive MA104 line, BFA caused beta- COP to be released from the Golgi complex in the presence of nucleotides, and either MA104 or PtK1 cytosol. In contrast, when perforated PtK1 cells were incubated with BFA, nucleotides, and cytosol from either cell type, beta-COP remained bound to the Golgi complex. We conclude that PtK1 cells contain a nondiffusible factor, which is located on or very close to the Golgi complex, and confers a dominant resistance to BFA. It is possible that this factor is homologous to the target of BFA in cells that are sensitive to the drug.